2010
DOI: 10.2174/1874126601004010055
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of the Activity of Gemcitabine-Loaded Pegylated Unilamellar Liposomes Against Papillary Thyroid Cancer Cells~!2010-04-18~!2010-06-27~!2010-08-23~!

Abstract: Papillary carcinoma is the most common form of malignant thyroid tumor. At present, a subset of these tumors are poorly responsive to the current treatment. Gemcitabine is a pyrimidine analog active against different types of solid tumors, but its use is limited by its short half-life. To improve the therapeutic effectiveness of this drug, gemcitabineloaded unilamellar pegylated liposomes were prepared and investigated against two human papillary thyroid carcinoma cell lines, i.e. TPC-1 and B-CPAP cells. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…21,54 Similar experiments were performed using other types of thyroid cancer cell lines (TPC-1, B-CPAP) with the aim of obtaining further evidence that the liposomal PEGylated formulation increases cellular uptake of gemcitabine and consequently amplifies its pharmacological effect. 51 This was confirmed by confocal laser scanning microscopy (CLSM); after 6 hours of incubation with fluorescein-labeled PEGylated liposomes, dissemination of the colloid was observed in all cellular compartments of the B-CPAP cells, including the cell membrane and cytoplasm, thus demonstrating internalization of the colloid ( Figure 6).…”
Section: In Vitro Antitumoral Activity Of Gemcitabine-loaded Liposomesmentioning
confidence: 61%
See 1 more Smart Citation
“…21,54 Similar experiments were performed using other types of thyroid cancer cell lines (TPC-1, B-CPAP) with the aim of obtaining further evidence that the liposomal PEGylated formulation increases cellular uptake of gemcitabine and consequently amplifies its pharmacological effect. 51 This was confirmed by confocal laser scanning microscopy (CLSM); after 6 hours of incubation with fluorescein-labeled PEGylated liposomes, dissemination of the colloid was observed in all cellular compartments of the B-CPAP cells, including the cell membrane and cytoplasm, thus demonstrating internalization of the colloid ( Figure 6).…”
Section: In Vitro Antitumoral Activity Of Gemcitabine-loaded Liposomesmentioning
confidence: 61%
“…36 This research showed that the PEGylated liposomal formulation had greater cytotoxic activity (evaluated as a function of drug concentration following 48 hours of incubation) than the free form of the drug, probably because encapsulation of the antitumoral compound in a liposomal system enabled greater intracellular uptake due to the ability of the vesicles to penetrate the cell membrane by fusion or endocytotic mechanisms. 11,51 Free gemcitabine did not have significant cytotoxic effects on the colon carcinoma cells at any of the experimental drug concentrations, while the liposomal formulation showed high antitumoral efficacy even at low drug concentrations. 36 Electrostatic charge and the presence of PEG moieties on the liposomal surface were the most important factors influencing interaction between the vesicular structures and the biological membranes.…”
Section: In Vitro Antitumoral Activity Of Gemcitabine-loaded Liposomesmentioning
confidence: 86%
“…170 For instance, a superior anticancer activity of PEGylated liposomal formulations of gemcitabine over the free drug was observed in various cancer cell lines in vitro. [171][172][173][174] The cytotoxicity of the formulation was evident after 12 h and 24 h of incubation whereas both higher drug concentrations and longer post-incubation times were needed to achieve a pharmacological effect with the free gemcitabine. This result was likely due to an improvement in cellular uptake of the drug which was confirmed by HPLC analysis and confocal laser scanning microscopy.…”
Section: Impaired Drug Uptakementioning
confidence: 99%